Exploring the catalytic efficiency of X‐doped (X=B, N, P) graphene in oxygen reduction reaction: Influence of solvent and border effects. Issue 14 (23rd December 2017) - Aguilar‐Galindo, Fernando; Ocón, Pilar; Poyato, José Manuel L.
Abstract: X doped graphene surfaces, where X is a heteroatom, are interesting for electrocatalytic applications in fuel cell because active sites are generated on the surface. In this work, a new large size surface is proposed to allow several heteroatoms to be located in positions far from the edge of the graphene sheet. Dispersion terms were introduced in the calculations which are crucial in adsorption processes. Natural charges are analyzed to determine the most active sites. A four‐electron transfer mechanism is assumed. The energies calculated for each step of the mechanism reveal that the P‐doped or the B‐doped surface are the ones that favors the oxygen reduction reaction the most, depending on the media. Abstract : The oxygen reduction reaction catalyzed by X‐doped graphene (X = B, N, P) is simulated in gas phase and in water media. A natural bond orbital analysis of the charge on the active sites is performed. The results show that the intrinsic catalytic activity is affected by the solvent and the best dopant atom depends on the medium.